Optimizing Project Management: Planning, Scheduling, and Cost Estimation Using Microsoft Project - Al-Dhamad, Saja Hadi Raheem; Kurwi, Sahar Ismael Baker; Varouqa, Ibrahim Farouq; Hayder, Gasim; Obaid, Aseel H.; Al-Zwainy, Faiq M. S. (Journal of Applied Science, Engineering, Technology, and Education, 2025)
Event or activity management is done with computer-based software built especially for planning and secluding, such Primavera, Microsoft Excel, and Microsoft Project. The MS project's scheduling and organization are the goals of this study. Software of this type is easier to use and more efficient than manual methods. Although this program is based on manual approaches, it is more accurate and takes less time. Scheduling should be created for this investigation. The project case study focuses on the planning and scheduling of residential construction. In this instance, a two-story, 200-square-meter residential building in Baghdad/Abi Ghraib, Iraq, was selected. A work schedule should be created in the Microsoft project from excavation to completion, alerting the crucial path. Every task and piece of material should have its resources allocated. The MS project should include a calculation of the material and labor costs. According to this study, the scheduling and Planning benefits should be clarified. This study aims to investigate and inform the appropriate planning and selection for project management using Microsoft Project. It will also inform the budget, material, time, and deadline.